The Cynics' Understanding of and Contribution to Philosophy - Hamouda, Yossra (AUC Knowledge Fountain, 2022)
The Cynics are an understudied school in the history of philosophy especially, if we compare the amount of literature written on the Cynics to the amount of literature written on Socrates, Plato, Aristotle and other Greek schools like the Epicureans, the Neo-Platonists and even the Stoics. The lack of research interest in the Cynics, both from the side of philosophers and historians, is possibly grounded in a lack of interest in understanding the Cynical conception of philosophy. Unless we take a serious interest in understanding the Cynical conception of philosophy, we risk reducing the Cynics to the historical clowns of philosophy. Indeed, considered from the outside, the Cynics may appear as mere comedians who were affected by Socrates. However, a serious interest in their conception of philosophy may allow us to better understand the Cynics, arrive at a deeper appreciation of their way of life and thus assign higher philosophical value to their thought. Another possible reason for the lack of interest and suitable appreciation towards the cynics, however, is the understanding of philosophy today. Philosophy is viewed as an elitist discipline. The ancient Greek understanding of philosophy as a way of life is thus foreign for many philosophical scholars. The appreciation of the Cynics’ school or even the fair judgement about it requires first an understanding of what philosophy as way of life means, how the Cynics view philosophy and what type of life the Cynics choose. This thesis thus studies the Cynics’ understanding of philosophy as a way of life. Part I of the thesis studies the Greek and Socratic understanding of philosophy. The Cynics’ understanding of philosophy is deeply affected by Socrates. Antisthenes, the founder of Cynicism, was Socrates’s student. Diogenes, the most influential and infamous figure in cynicism, described himself as “a Socrates gone Mad.” The first part of the thesis gives an overview of the Greek socio-political, religious and philosophical conditions prior to the emergence of the Cynics and during their lives. It also seeks to understand the Cynics’ reasons for their conduct and distinctive lifestyle. Part II of the thesis shows a panorama of different philosophical and artistic perspectives on the Cynics. This part thus tries to identify the motives working towards the constitution of the image of the Cynics in the history of philosophy. It presents ancient and modern philosophers' perspective on the Cynics but also French Enlightenment writers’ and playwrights’ image of the Cynics. Part III of the work is dedicated to the two primary sources used in this thesis: The Lives and Opinions of Eminent Philosophers and Dio Chrysostom’s Discourses 1-11. Part III presents all the available information about these two primary sources. The core of the thesis is Part IV, which discusses the Cynics’ understanding of philosophy as a way of life. Part 4 is divided into three sections. The first section gives a detailed explanation of what philosophy as a way of life means. The second section shows how the Cynics perform philosophy as a way of life. The third section, finally, gives a comprehensive account of the Cynics’ way of life from its constitutive aspects.